2024
DOI: 10.1002/hed.27711
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of bone marrow and tumor 18F‐FDG uptake on PET/CT in patients with oropharyngeal cancer and the interplay between inflammation and FDG uptake

Constantina Nadia Christou,
Karl Sandström,
Naresh Regula
et al.

Abstract: AimsTo examine the prognostic value of F‐18 fluorodeoxyglucose (FDG) uptake in the bone marrow (BM) for disease recurrence and survival in patients with oropharyngeal squamous cell carcinoma (OP‐SCC). The secondary aims were to evaluate the prognostic value of PET/CT parameters for the primary oropharyngeal tumor and total tumor burden, and to assess the correlation between FDG uptake variables and serum inflammatory markers.MethodsThis was an observational study of 91 patients with OP‐SCC who underwent pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition to BM SUV, BLR, and BAR have been used as PET/CT imaging parameters for the BM to mitigate the variations in BM FDG uptake among individuals [13,15,30]. Several previous studies have demonstrated that BLR exhibited superior prognostic value compared to BM SUV in predicting clinical outcomes across various types of cancers, including head and neck cancer, breast cancer, non-small cell lung cancer, and gastric cancer, and only a single study focusing on cervical cancer demonstrated the significant prognostic value of BAR [14,15,19,31]. However, the results of this study indicate the superior prognostic value of BAR compared to that of BLR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to BM SUV, BLR, and BAR have been used as PET/CT imaging parameters for the BM to mitigate the variations in BM FDG uptake among individuals [13,15,30]. Several previous studies have demonstrated that BLR exhibited superior prognostic value compared to BM SUV in predicting clinical outcomes across various types of cancers, including head and neck cancer, breast cancer, non-small cell lung cancer, and gastric cancer, and only a single study focusing on cervical cancer demonstrated the significant prognostic value of BAR [14,15,19,31]. However, the results of this study indicate the superior prognostic value of BAR compared to that of BLR.…”
Section: Discussionmentioning
confidence: 99%